Healthy Eating and Physical Activity Policy, Systems, and Environmental Strategies: A Content Analysis of Community Health Improvement Plans - Sreedhara, Meera; Goulding, Melissa; Valentine Goins, Karin; Frisard, Christine; Lemon, Stephenie C. (Frontiers in Public Health, 2020)
Abstract Background: Policy, systems, and environmental (PSE) approaches can sustainably improve healthy eating (HE) and physical activity (PA) but are challenging to implement. Community health improvement plans (CHIPs) represent a strategic opportunity to advance PSEs but have not been adequately researched. The objective of this study was to describe types of HE and PA strategies included in CHIPs and assess strategies designed to facilitate successful PSE-change using an established framework that identifies six key activities to catalyze change. Methods: A content analysis was conducted of 75 CHIP documents containing HE and/or PA PSE strategies, which represented communities that were identified from responses to a national probability sample of US local health departments (<500,000 residents). Each HE/PA PSE strategy was assessed for alignment with six key activities that facilitate PSE-change (identifying and framing the problem, engaging and educating key people, identifying PSE solutions, utilizing available evidence, assessing social and political environment, and building support and political will). Multilevel latent class analyses were conducted to identify classes of CHIPs based on HE/PA PSE strategy alignment with key activities. Analyses were conducted separately for CHIPs containing HE and PA PSE strategies. Results: Two classes of CHIPs with PSE strategies emerged from the HE (n=40 CHIPs) and PA (n=43 CHIPs) multilevel latent class analyses. More CHIPs were grouped together in Class A (HE: 75%; PA: 79%), which were characterized by PSE strategies that simply identified a PSE solution. Fewer CHIPs were grouped in Class B (HE: 25%; PA: 21%), and these mostly included PSE strategies that comprehensively addressed multiple key activities such as the critical step of assessing social and political environment for PSE-change. Conclusions: Few CHIPs containing PSE strategies addressed multiple key activities for PSE-change. Efforts to enhance collaborations with important decision-makers and community capacity to engage in a range of key activities are warranted.